Transforming Terrestrial Defense Doctrines In Response To Cyber And Space Domain Threats - Lusiana Dwiyanti; Robby MT; Guntur Eko Saputro (PALAR | PAKUAN LAW REVIEW, 2026)
In the era of multidomain warfare, conventional land defense doctrines encounter fundamental challenges stemming from the proliferation of cyber and space threats, which obscure traditional operational boundaries and accelerate the dynamics of asymmetric conflicts. The background of this study is rooted in the inadequacy of national military doctrines to counter hybrid attacks, wherein cyber incidents such as breaches of defense networks and satellite interference jeopardize the integrity of land operations, as evidenced by post-2020 escalations in the Indo-Pacific region. This research aims to analyze the transformation of land defense doctrines in order to integrate resilience across cyber and space dimensions, while formulating policy recommendations aligned with the national defense vision, with a particular emphasis on strategic adaptation and multidomain operations (MDO) to bolster national resilience. Methodologically, the study adopts a qualitative approach, employing thematic analysis of policy documents and strategic frameworks. The findings reveal the necessity for a fundamental restructuring of land defense doctrines across three domains: conceptual adaptation to the multidomain warfare paradigm, technological modernization of critical defense infrastructure, and institutional reform of command and control structures. The study's conclusion affirms that successful doctrine transformation demands the implementation of an integrated Multidomain Operations framework, substantial investments in cyber-space capabilities, and strategic partnerships with national and international stakeholders. Keywords: Doctrine Transformation, Cyber Threats, Outer Space, Multidomain Operations, Indonesian Land Defense.